Regression residual control chart for monitoring academic performance of students in higher learning institution / Nurazlina Abdul Rashid...[et al.] - Abdul Rashid, Nurazlina; Wan Hassan, Wan Hasni Sabariah; Che Hussin, Wan Siti Esah (2013)
Students ' academic performance is an important determinant of his/her future success. The students ' cumulative grade point average (CGPA) is a common measured by most universities and is a crucial factor in admission to postgraduate program and access to job markets. Nowdays, number of students in institutions of higher learning increase every year but the quality has still to be maintained and will not be sacrifice at all means. At present, there is no system for monitoring students ' performance. So, this study proposed to come up with a system to monitor students' performance. One of the critical quality characteristics used to measure the quality of a student is their academic performance.